Assessing Impression Management With the MMPI-2 in Child Custody Litigation. (December 2015) - Arce, Ramón; Fariña, Francisca; Seijo, Dolores; Novo, Mercedes
Forensic psychological evaluation of parents in child custody litigation is primarily focused on evaluating parenting capacity and underreporting. The biased responses of underreporting have been classified as Impression Management (IM) or as Self-Deceptive Positivity (S-DP), which are regarded to be conscious or unconscious in nature, respectively. A field study was undertaken to assess impression management on the Minnesota Multiphasic Personality Inventory–2 (MMPI-2) in child custody cases, the accuracy of the MMPI-2 scales in classifying IM, and what parents in child custody litigation actually manipulate in terms of IM. A total of 244 parents in child custody litigation and 244 parents under standard instructions were administered the MMPI-2. The results revealed that the L, Mp, Wsd, and Od scales discriminated between both samples of parents; the rate of satisfactory classification (i.e., odds ratio ranged from 5.7 for Wsd to 23.3 for Od) and an incremental validity of Od over Mp and Wsd. As for the effects of IM, the results show IM effects in the Basic Clinical Scales, the Restructured Clinical Scales, the Personality Psychopathology Five Scales, the Content Scales, and the Supplementary Scales. The implications of the results are discussed in relation to the forensic evaluation of parents in child custody litigation.